Odor Localization and Sniffing - Frasnelli, Johannes; Charbonneau, Genevieve; Collignon, Olivier; Lepore, Franco (Chemical senses, 2009)
For humans, the localization of an odorant seems only possible if the odorant also stimulates the trigeminal nerve. There is, however, some evidence that active sniffing may affect this ability and facilitate the localization of pure odorants. Therefore, we tested the ability of 40 subjects to localize a pure odorant and a mixed olfactory/trigeminal stimulus under 2 stimulation conditions: either odors were blown into the subjects’ nostrils (passive) or subjects had to actively sniff the odors (active). Subjects could only reliably localize the mixed olfactory/trigeminal stimulus. However, we found a significant interaction between stimulation condition and nature of the odorant. So, the mixed olfactory/trigeminal stimulus was more localizable in the passive condition, whereas the pure odorant was better localized in the active condition. Interestingly, subjects had more correct answers after stimulation of the right nostril than of the left nostril (where subjects performed significantly below chance when stimulated with the pure odorant), suggesting possible laterality effects. These results suggest that active sniffing may affect our ability to localize odors. Other than mixed olfactory trigeminal stimuli, pure odorants are, however, not localizable even in active condition of sniffing.